Does time from diagnosis to treatment affect the prognosis of patients with newly diagnosed acute myeloid leukemia? - Röllig, Christoph; Krämer, Alwin; Müller-Tidow, Carsten; Schliemann, Christoph; Mikesch, Jan-Henrik; Steffen, Björn; Krämer, Alwin; Noppeney, Richard; Schäfer-Eckart, Kerstin; Krause, Stefan W.; Hänel, Mathias; Herbst, Regina; et al. (Blood, 2020)
leukemia, myelocytic, acute, time-to-treatment, disease remission, genetics, follow-up, leukemia, acute, acute promyelocytic leukemia
Gesehen am 23.09.2020